PENYEMBUHAN LUKA BAKAR PADA TIKUS PUTIH DENGAN MENGGUNAKAN EKSTRAK DAUN PEGAGAN (CENTELLA ASIATICA) 25% DAN EKSTRAK DAUN PETAI CINA (LEUCAENA LEUCOCEPHALA) 30% - Syaifuddin Kurnianto; Kusnanto Kusnanto; Padoli Padoli (Universitas Nahdlatul Ulama Surabaya, 2017)
Burns are one of the injuries that require the best care to achieve optimal cure. Several previous studies have suggested that leaf extract of Centella asiatica and chinese petai leaf potential as burning healing agent for mild and moderate degree besides medical treatment. The purpose of this study was to explain the difference of effectiveness of leaf extract of pegagan leaves 25% by giving 30% petai chinese extract to heal burns. The samples were white rats (Rattus norvegicus) with total of 28 tails selected according to inclusion criteria then divided into 4 groups randomly is group of leaf extract of pegagan leaf 25% (K1), 30% petai petroleum extract (K2) Gel base (K3) and control (K4). The design of this study used the randomized posttest only control group design and analyzed using Anova and post Hoc Duncan test. The measured variable is the duration of wound healing. Anova test results and Post Hoc Duncan test duration of burn wound healing show that 30% Chinese petai extract group has significant difference with other group with p-value <0,05. Treatment of burns by using chinese petroleum extract 30% more effective than 25% of pegagan leaf extract in healing burns in white rats (Rattus norvegicus) as evidenced by the fastest healing time of burns.